Indirect evidence of sex-selective abortion practices to the imbalanced sex ratio at birth in Australian migrant populations. - Amanuel Tesfay Gebremedhin; Gizachew A Tessema; Ravisha Srinivasjois; Judith A Daire; Kevin A Chai; Bereket Duko; Kalayu Brhane Mruts; Gavin Pereira (PLOS Global Public Health)
A skewed sex ratio at birth (SRB), commonly observed in countries with high son preference can be attributed to prenatal sex-selective abortion. However, the possibility of sex selection among migrants in high-income countries has received little attention. Our study aims to identify the indirect evidence of sex-selective abortion practices to the SRB imbalance in a large Australian cohort. Our study aims to identify the indirect evidence of sex-selective abortion practices to the SRB imbalance in a large Australian cohort. In this population-based study, perinatal data were obtained from all registered births in Western Australia (WA) and New South Wales (NSW) for the period 1994 - 2015 (N = 2,175,252 births). We estimated the male-to-female sex ratio at birth (SRB) and 95% CI by mothers' country of birth stratified by sex of previous child and parity. The SRB exceeded expectations for children born to Indian, Chinese and Vietnamese mothers. For mothers from China, the SRB was 1.09 at second birth, slightly varying by sex of previous child (1.07 for male, 1.11 for a female) and markedly higher (1.34) at the third birth when the first two were female. A similar pattern was observed for Indian-born mothers. Indian and Chinese mothers had much higher induced abortion rates in early pregnancy than their Australian counterparts, which coincided with the introduction of non-invasive prenatal testing. Our study provides observational evidence that linked the male-biased SRB with prenatal sex determination followed by selective female-biased abortion practices. The findings of this study can inform public health policy decisions to address imbalanced SRB and sex-selective practices among migrants in high-income countries.